Black Women’s Journey in America and the Need for Intersectionality: A Comparative Reading of Maya Angelou’s “Still I Rise”, Lucille Clifton’s “won’t you celebrate with me” and June Jordan’s “Poem About My Rights” - Damas, Ana Rafaela (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2023)
Through a comparative reading of Maya Angelou’s “Still I Rise”, Lucille Clifton’s “won’t you celebrate with me” and June Jordan’s “Poem About My Rights”, this essay aims to analyse the black women’s journey in America, by considering their identity and the adversities they faced during their path under the light of Kimberlé Crenshaw’s concept of “intersectionality”.